AERIAL APPLICATION OF Bacillus thurigiensis AGAINST THE VELVETBEAN CATERPILLAR, Anticarsia gemmatalis HUEBNER, IN SOYBEAN FIELDS - Habib, M. E. M.; Amaral, M. E. C. (REVISTA DE AGRICULTURA, 2015)
AERIAL APPLICATION OF Bacillus thurigiensis AGAINST THE VELVETBEAN CATERPILLAR, Anticarsia gemmatalis HUEBNER, IN SOYBEAN FIELDS